Portuguese food composition database quality management system - Oliveira, L. M. (2011)
BACKGROUND: The harmonisation of food composition databases (FCDB) has been a recognised need among users, producers and stakeholders of food composition data (FCD). To reach harmonisation of FCDBs among the national compiler partners, the European Food Information Resource (EuroFIR) Network of Excellence set up a series of guidelines and quality requirements, together with recommendations to implement quality management systems (QMS) in FCDBs. The Portuguese National Institute of Health (INSA) is the national FCDB compiler in Portugal and is also a EuroFIR partner. INSA's QMS complies with ISO/IEC (International Organization for Standardisation/International Electrotechnical Commission) 17025 requirements. The purpose of this work is to report on the strategy used and progress made for extending INSA's QMS to the Portuguese FCDB in alignment with EuroFIR guidelines. SUBJECTS/METHODS: A stepwise approach was used to extend INSA's QMS to the Portuguese FCDB. The approach included selection of reference standards and guides and the collection of relevant quality documents directly or indirectly related to the compilation process; selection of the adequate quality requirements; assessment of adequacy and level of requirement implementation in the current INSA's QMS; implementation of the selected requirements; and EuroFIR's preassessment 'pilot' auditing. RESULTS: The strategy used to design and implement the extension of INSA's QMS to the Portuguese FCDB is reported in this paper. The QMS elements have been established by consensus. ISO/IEC 17025 management requirements (except 4.5) and 5.2 technical requirements, as well as all EuroFIR requirements (including technical guidelines, FCD compilation flowchart and standard operating procedures), have been selected for implementation. The results indicate that the quality management requirements of ISO/IEC 17025 in place in INSA fit the needs for document control, audits, contract review, non-conformity work and corrective actions, and users' (customers') comments, complaints and satisfaction, with minor adaptation. Implementation of the FCDB QMS proved to be a way of reducing the subjectivity of the compilation process and fully documenting it, and also facilitates training of new compilers. Furthermore, it has strengthened cooperation and trust among FCDB actors, as all of them were called to be involved in the process. CONCLUSIONS: On the basis of our practical results, we can conclude that ISO/IEC 17025 management requirements are an adequate reference for the implementation of INSA's FCDB QMS with the advantages of being well known to all members of staff and also being a common quality language among laboratories producing FCD. Combining quality systems and food composition activities endows the FCDB compilation process with flexibility, consistency and transparency, and facilitates its monitoring and assessment, providing the basis for strengthening confidence among users, data producers and compilers.